Integrative analysis of microbiota and metabolomics in chromium-exposed silkworm (Bombyx mori) midguts based on 16S rDNA sequencing and LC/MS metabolomics - Chen, Ya-Zhen; Rong, Wan-Tao; Qin, Ying-Can; Lu, Lin-Yuan; Liu, Jing; Li, Ming-Jie; Xin, Lei; Li, Xiao-Dong; Guan, De-Long (Frontiers in Microbiology, 2023)
The gut microbiota, a complex ecosystem integral to host wellbeing, is modulated by environmental triggers, including exposure to heavy metals such as chromium. We comprehensively explored chromium-induced gut microbiota and metabolomic shifts in the quintessential lepidopteran model organism, the silkworm (Bombyx mori), via deploying 16S rDNA sequence analysis and LC/MS metabolomics. The experimental design encompassed a control group alongside low (12 g/kg) and high (24 g/kg) oral chromium dosing regimens. Our findings underscored considerable heterogeneity in microbial diversity between cohorts. Weissella emerged as potentially resilient to chromium stress, while elevated Propionibacterium was noted in the high chromium treatment group. Key species, identified via differential analysis tools LEfSe and random forest estimation, like Cupriavidus and unspecified Myxococcales, offered potential avenues for bioremediation. An examination of gut functionality brought to light alterations in the KEGG pathways correlated with biosynthesis and degradation, hinting at an adaptive metabolic response to chromium-mediated stress. The consequential fallout was also captured in the context of metabolomic alterations. Among the identified differential metabolites were an uptick in histidine and dihydropyrimidine levels under moderate-dose exposure and a surge of gentisic acid with high-dose chromium exposure -critical players in diverse biological processes ranging from energy metabolism and stress response to immune regulation and antioxidative mechanisms. Correlative analyses between bacterial abundance and metabolites mapped noteworthy relationships between marker bacterial species, such as Weissella and Pelomonas, with specific metabolites, emphasizing their roles in enzyme regulation, synaptic processes, and lipid metabolism. Probiotic bacteria showed robust correlations with metabolites implicated in stress response, lipid metabolism, and antioxidant processes. Collectively, our study reaffirms the intricate ties between gut microbiota and metabolite profiles and decodes some systemic adaptations under stress, lending valuable insights into the ecological and toxicological aspects of chromium exposure that potentially influence silkworm resilience.